THE INFLUENCE OF GEOPOLITICS ON THE INTERNATIONAL RAIL SERVICE OF UKRAINE - Савчук, І. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2018)
Geopolitics directly affects the state and level of development of the international railway communication of Ukraine. The evidence of this is the political and military events of recent years, which have led to fundamental changes in the direction and structure of passenger transportation in the international railway communication of the state. Thus, Ukrzaliznytsya is to direct its efforts to use the advantageous transport and geographical position of the state in Europe to ensure the growth of exports of services on railway passenger transportation. Keywords: geopolitics, railway communication, passenger transport.